Carboxypeptidase B1 in dialyzed chronic kidney disease patients - Matej Stančík; Marián Grendár; Marián Mokáň (Scientific Reports)
Abstract Carboxypeptidase B1 has long been known to be a pancreas-specific tissue enzyme. In this paper we focus on Carboxypeptidase B1 concentration measurement in dialyzed chronic kidney kidney disease patients and on the effect dialysis adequacy and regimen exert on its concentration. A total of 142 subjects were divided into control and target groups. In the target group two measurements of plasma Carboxypeptidase B1 one month apart were conducted with the use of Carboxypeptidase B1 ELISA kit. The mean Carboxypeptidase B1 concentration was significantly higher in the target arm compared to the control arm (77.60 ± 11.81 ng/mL and 1.22 ± 0.41 ng/mL, respectively; p < 0.001). Generalized linear mixed regression revealed that affiliation with the control arm was the only significant contributor of this finding. Linear mixed model regression revealed that dialysis regimen that represents number of dialyses per one week-long cycle is a significant predictor of Carboxypeptidase B1 concentration. Exploration of the estimated marginal means of Carboxypeptidase B1 revealed that the Carboxypeptidase B1 concentration was significantly higher among patients on twice per week dialysis regimen than among those treated with three dialysis sessions per week.